(3cJGH aj GdMOjKs
(3ChdgG (B:s
(3GdMeO ddg GdhGLH MeOg hHYO agPG JYdjb bUOJ Hg GdJYdjb HGdLfGH GdYdi hGdEVGaI HGdNOeI Edi GdNGFVjf ai GdMOjK GdfHhi GYde s
(3BNQgG (B:s
(3hbO hQOJ efg BKGQ efgG ef JhGVY Gddg QaYg Edjg hefgG ai ebGHdg hGdYjGP HGddg ef JcHQ dZjQ Mb ChQKI dGdg PdkG HMb eeG hQO ai Pdc CQHY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdeLGejYs